Analisis Teori Hukum Alam dalam Perspektif Filsafat Hukum dan Relevansinya bagi Pemikiran Hukum di Indonesia - Asnawi, M. Natsir; Aryandita, Nanda; Besmar, Muhammad Sakial; Agnes, Linda; Radityo, Robertus Bellarmino Yordan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research examines the contribution and relevance of natural law in establishing a just legal system in Indonesia, particularly within the framework of human rights protection. Using a normative juridical approach and a literature review of both classical and modern legal philosophy, this article explores natural law principles as a universal and timeless moral foundation. The research findings demonstrate that natural law, both in its irrational form derived from divine values and its rational form rooted in human reason, has significant capacity to strengthen the legitimacy of Indonesian positive law. Integrating natural law values into the national legal system faces structural and cultural challenges, but still presents opportunities through strengthening regulations based on substantive justice, recognizing customary law, and implementing the principle of restorative justice. This research recommends harmonizing positive law and natural law principles as a strategy for more inclusive legal reform oriented toward respect for human dignity.